2009
DOI: 10.1111/j.1464-5491.2009.02810.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction models for the development of diabetes in Mauritian Indians

Abstract: A diabetes prediction model based on obesity and family history yielded moderate discrimination in Mauritian Indians, which was slightly inferior to the model with the FPG but may be useful in low-income countries to promote identification of people at high risk of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Combining information on FPG or impaired fasting glucose with a simple diabetes risk score has been reported to increase predictive ability [7,8,[12][13][14][15][16][17]. A study reported that screening models using the combination of HbA 1c , BMI and FPG accurately identified individuals at risk of future clinically diagnosed diabetes [22], although the factors that remained significant were different from those found in the present study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Combining information on FPG or impaired fasting glucose with a simple diabetes risk score has been reported to increase predictive ability [7,8,[12][13][14][15][16][17]. A study reported that screening models using the combination of HbA 1c , BMI and FPG accurately identified individuals at risk of future clinically diagnosed diabetes [22], although the factors that remained significant were different from those found in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…Various rules have been developed to predict the incidence of diabetes in different ethnic groups [2][3][4][5]. Routine clinical markers available without laboratory testing have been shown to be predictive of the development of diabetes [6][7][8][9][10][11][12][13][14][15][16][17][18] and adding biochemical measures, in particular fasting plasma glucose (FPG), improves predictive accuracy [7,8,[12][13][14][15][16][17]. On the other hand, adding complex data such as the results of oral glucose tolerance tests and measurements of insulin levels and inflammatory markers into a simple clinical model only minimally improves risk prediction while increasing cost and inconvenience [10,19].…”
Section: Introductionmentioning
confidence: 99%
“…This difference seemed attributable to the different BMI-adjusted education–DM associations found in LICs versus MICs as well. Different from LICs, higher education level has been associated with decreased odds of DM among Mauritian Indians23 and people in Lithuania 24. Even accounting for BMI, such negative education–DM association was found in studies done in Brazil25 and China 26.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies reported examining the association of individual risk predictors with patient outcome after adjusting for age and sex [27] and age and cohort [30]. Nine studies (23%) included all risk predictors in the multivariable analysis [25,26,33,36,39,49,51,53,61].…”
Section: Resultsmentioning
confidence: 99%